Novel covalent organic nanosheets for the construction of ultrafine and well-dispersed metal nanoparticles. (11th August 2020) - Lu, Feipeng; Li, Yaqiong; Shi, Qingrong; Zhao, Chaofeng; Li, Shenghua; Pang, Siping
Abstract : CON–DAI–TFP, a pyrazole-functionalized nanosheet structure, demonstrates an efficient strategy for the synthesis of ultrafine, highly dispersed, and high loading U-MNPs, which are urgently needed in industrial and laboratory catalysis. Abstract : The development of supported and well-dispersed ultrafine metal nanoparticles (U-MNPs) with high metal content is a research priority, yet remains a significant challenge. Herein, we propose an effective strategy involving functional covalent organic nanosheets (CONs) to construct well-dispersed U-MNPs. To construct the corresponding CON–DAI–TFP, 4, 7-diamino-1 H -indazole (DAI) and 1, 3, 5-triformylphloroglucinol (TFP) are strategically chosen as precursors. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM) clearly confirm the nanosheet structure of CON–DAI–TFP . CON–DAI–TFP is used as a substrate to immobilize Pd nanoparticles (Pd-NPs). The supported Pd-NPs are ultrafine, highly dispersed, and possess high metal content (average size, 1.74 nm; metal content, 20.47 wt%), which is superior to many of the reported supported Pd-NPs. Moreover, the supported Pd-NPs show excellent catalytic activity and recyclability in a p -nitrophenol reduction reaction. In addition to Pd-NPs, this strategy can be applied to produce other U-MNPs with similar features, including Ir-NPs and Pt-NPs (1.99 nm and 17.18 wt% for Ir-NPs, 2.25 nm and 29.46 wt% for Pt-NPs), suggesting that this strategy is universal. For comparison, a bulk COF (COF–DAI–TFB ), the analogue of CON–DAI–TFP, is designed and synthesized. In contrast, many large Pd-NPs with an average size of 17.86 nm, which is more than 10 times the size of Pd-NPs on CON–DAI–TFP, are observed on the surface of the COF–DAI–TFB . This result further confirms the significance of CONs in the preparation of well-dispersed and high-loading U-MNPs.